A redescription of a rare axiid shrimp, Amakusaxius amakusanus (Miyake & Sakai, 1967) (Crustacea: Decapoda: Axiidea) from new material collected off Taiwan - Komai, Tomoyuki; Chan, Tin-Yam; Shy, Jhy-Yun (Zootaxa, 2013)
Miyake & Sakai (1967) described a new species of axiid shrimp, Calocaris (Calastacus) amakusana, from a single female specimen lacking a major cheliped. Later, Sakai & de Saint Laurent, 1989 transferred this species to their new genus Acan-thaxius. However, Sakai (2011) recently established a new monotypic genus Amakusaxius to accommodate Acanthaxius amakusana. Since the original description no additional specimen of this rare species has been reported and consequently an appraisal of A. amakusanus (Miyake & Sakai, 1967) has not been possible. Now six specimens including three males and three ovigerous females have been collected from Taiwan. This has enabled the diagnostic characters of the species to be fully evaluated. The presence of a postcervical median carina on the carapace, weak armature on the major cheliped, and the morphology of the uropod are characters that distinguish Amakusaxius from Acanthaxius. Consequently the mo-notypic genus Amakusaxius Sakai, 2011 is retained.